2014
DOI: 10.3390/ijms151119330
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations rs11892031 and rs401681 Are Associated with Bladder Cancer Risk in a Chinese Population

Abstract: Genome-wide association studies (GWAS) have identified a number of genetic variants associated with risk of bladder cancer in populations of European descent. Here, we assessed association of two of these variants, rs11892031 (2q37.1 region) and rs401681 (5p15.33 region) in a Chinese case-control study, which included 367 bladder cancer cases and 420 controls. We found that the AC genotype of rs11892031 was associated with remarkably decreased risk of bladder cancer (adjusted odds ratio (OR), 0.27; 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…However, a recent study reported that CLPTM1L is a commonly overexpressed anti-apoptotic factor in lung cancer [30,32]. Our study and previous research suggest that one SNP can be associated with two or more cancers; for example, rs401681 is associated with many cancers including pancreatic cancer, lung cancer, bladder cancer, and hepatocellular carcinoma [33][34][35]. Further studies are needed to clarify the genetic mechanism of esophageal carcinogenesis by fine mapping the susceptibility region of the variants.…”
Section: Discussionmentioning
confidence: 58%
“…However, a recent study reported that CLPTM1L is a commonly overexpressed anti-apoptotic factor in lung cancer [30,32]. Our study and previous research suggest that one SNP can be associated with two or more cancers; for example, rs401681 is associated with many cancers including pancreatic cancer, lung cancer, bladder cancer, and hepatocellular carcinoma [33][34][35]. Further studies are needed to clarify the genetic mechanism of esophageal carcinogenesis by fine mapping the susceptibility region of the variants.…”
Section: Discussionmentioning
confidence: 58%
“…Bladder cancer is the second most common urological malignancy in the US and is by far the most frequently diagnosed urological malignancy in China. Epidemiological data provided by the International Agency for Research on Cancer (IARC) in 2012 reported 55,486 cases and 26,820 deaths of bladder cancer in China (1). A total of 740,000 new cases and 16,000 deaths caused by bladder cancer were recorded in 2015 in the US (2).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have identified 17 independent loci and single nucleotide variants (SNVs) that contribute to bladder cancer susceptibility in European population [(8-14); Table S1]. Many loci have been replicated in additional studies, and additional new loci found to be, associated with bladder cancer risk in Chinese population (15)(16)(17)(18)(19)(20)(21). GWA studies have been successful in identifying common variants involved in complex trait etiology.…”
Section: Introductionmentioning
confidence: 99%